Chinese Herbal Extracts Exert Neuroprotective Effect in Alzheimer’s Disease Mouse Through the Dopaminergic Synapse/Apoptosis Signaling Pathway - Huang, Qianqian; Zhang, Chen; Qu, Sihao; Dong, Shi; Ma, Qihong; Hao, Ying; Liu, Zimin; Wang, Shanglong; Zhao, Haibin; Shi, Yuanyuan (Frontiers in Pharmacology, 2022)
Background Alzheimer's Disease (AD) as an age-related, irreversible neurodegenerative disease, characterized by cognitive dysfunction, has become progressively serious in life. With the failure of drug elaboration, therapeutic strategies using traditional Chinese medicine are under investigation for AD treatment. Gastrodia, elata Blume, Polygala tenuifolia Willd., Cistanche deserticola Ma, Rehmannia lutinosa (Gaertn.)DC.,Acorus gramineus Aiton, and Curcuma longa L. are well-known Chinese herbs with neuroprotective effects and widely used as a combination in traditional Chinese decoction for AD treatment. The purpose of this study was to investigate the synergistic protective efficacy of the combination (composed of extracts from these six Chinese medicines), and the protein targets on scopolamine-induced cognitive impairment, using the proteomics analysis. Methods Scopolamine-induced cognitive impairment mouse model was established. Behavioral tests, cerebral cholinergic system alterations were examined to evaluate the ameliorating effects of GPCEAC extrccts on scopolamine induced-cognitive impairment. To identify the potential molecular mechanism mediated by GPCRAC extracts in treating AD, label-free quantitative proteomics coupled with tandem mass spectrometry (LC-MS/MS) were performed. The integrated bioinformatics analysis was applied to screen the core differentially expressed proteins in vital canonical pathways. Critical altered proteins were validated by qPCR and Western blotting. Results Administration of GPCRAC extracts significantly recovered scopolamine-induced cognitive impairment, as evidenced by the improved learning and memory ability, increased Ach content and ChAT activity, as well as decreased AchE activity in the hippocampus of mice. In total, 390 proteins were identified as significant differentially expressed proteins, of which 110 were significantly up-regulated and 25 were significantly down-regulated between control and model group. By mapping the significantly regulated proteins, we identified five hub proteins: PPP2CA, Gsk3β, PP3CC, PRKACA, and BCL2 that were associated with dopaminergic synapse and apoptosis signaling pathway, respectively. Western blotting and qPCR demonstrate that the expression levels of these core proteins could be significantly improved by the administration of GPCRAC. Conclusions Administration of GPCRAC extracts was effective on alleviating scopolamine-induced cognitive impairment, which might be through modulation of dopaminergic synapse and apoptosis signaling pathway. Consequently, our quantitative proteome data obtained from scopolamine-treated model mice successfully characterized AD-related biological alterations and proposed novel protein biomarkers for AD.